US-China tech decoupling increases willingness to share personal data in China - Yong Suk Lee; Benjamin Cedric Larsen; Jingxin Wu (Humanities & Social Sciences Communications)
Abstract Conflicts involving tech companies and data privacy between the US and China have evolved into a technology decoupling between the two countries. Nationalistic sentiments have been on the rise in both countries as well. This study examines how the rising geo-technological race and conflict affect people’s perception of data privacy. In particular, we examine whether reminding Chinese internet users of the US-China technological decoupling influences their willingness to share personal data. We conduct a randomized online experiment where we remind people of the US–China technology competition in artificial intelligence or the US sanctions on Chinese tech companies and examine the impact on respondents’ willingness to share personal data with private companies, the central government and local government. We find that the US-China tech decoupling treatments increase people’s willingness to share their data with private companies. Exploring the heterogeneous treatment effects by gender and education level reveals that nationalism is likely the mediating factor that explains why some people, especially, males and the college educated, are more likely to increase their willingness to share personal data when exposed to these treatments. Moreover, the US-China tech decoupling treatments directly increase people’s perception that data is a key input for Chinese company competitiveness in AI development. In sum, we find that reminding people of the US-China tech decoupling can invoke nationalistic sentiment and increase people’s willingness to share data with private companies and the government in China. The randomized control trial was pre-registered on the AEA RCT Registry (AEARCTR-0007526). The public URL of https://www.socialscienceregistry.org/trials/7526 and the digital object identifier (DOI) is 10.1257/rct.7526-1.0.